Blue's big parade! - Spelvin, Justin; Johnson, Traci Paige; Kessler, Todd.; Santomero, Angela C.; Chernichaw, Ian (New York, N.Y. : Simon Spotlight/Nick Jr., 2005)
Blue and her friends prepare for the summer parade by making hats, floats, and instruments.
"Based on the TV series Blue's Clues created by Traci Paige Johnson, Todd Kessler, and Angela C. Santomero"--T.p. verso.
003-007.
87370
Keywords: Blue (Fictitious character) -- Juvenile fiction; Parades -- Juvenile fiction; Dogs -- Juvenile fiction; Summer -- Juvenile fiction; Blue (Fictitious character) -- Fiction; Parades -- Fiction; Dogs -- Fiction; Summer -- Fiction; Radio and television novels